Funnel chest. Surgical correction - Brandolino, Mario V.; Bertullo, Hugo; Pomi, Jorge; Nin Vivó, Jorge (Cirugía del Uruguay, 1986)
The funnel chest is an esternocondrocostal malformation adopting two predominant forms, one deep central symetric and, another, wider and asymmetric. Presentation of eleven operated cases of the former, with considerations on theirs pathogeny, indications of surgery and surgical techique. Results obtained were very good. There was an inflamatory complication resolved without consequences.